Biokonsentrasi Faktor Logam Berat Kromium Heksavalen (Cr VI) Pada Ikan Nila (Oreochromis niloticus) di Sungai Tenggang Semarang Timur - Vitasari, Marliana; Darundiati, Yusniar Hanani; Setiani, Onny (Jurnal Ilmiah Mahasiswa, 2020)
Title: Bioconcentration of Hexavalent Chromium (Cr VI) Heavy Metal Factor in Tilapia (Oreochromisniloticus) in Tenggang River, East SemarangBackground: Tenggang River is one of drainages in the eastern Semarang city while Tenggang River potential for aquaculture activities. Water quality is one of important parameter for aquaculture and safe fish for human consumption. Tenggang River is in contact with the Bugangan Small Industrial Environment (LIK) which asks for heavy metal pollution in the Tenggang River body. Methods: The precence of heavy metal Kromium hexavalent was found on water of Tenggang River.Â  Measurement of kromium heavy metal content in the air and fish using the Atomic Absorption Spectrophotometry (AAS) method. Result: The results showed that the average of hexavalent kromium concentration in the Tenggang RiverÂ  was approved by PP No 82 of 2001 quality standard which was 0.1256 mg/l and the average hexavalent kromium levels in tilapia meat in the Tenggang River could also be exchanged for quality WHO FAO is 0.1 mg/kg. Conclusions: Bioconcentration factor of tilapia in the Tenggang River is 31,22l. Based on the BCF Metal Cr VI category included in the low category.